The Influence of Andropause on Incidence of Depression in Males at Subdistrict Jebres, Surakarta - Iriyanti Maya Sari Barutu; . Mujosemedi; Andri Iryawan (Nexus Kedokteran Komunitas, 2015)
Background: One of the symptoms in males with andropause is mood depression. Andropauses occurrence in a man may increase the incidence of depression. This research aimed to know the influence of andropause on incidence of depression in males at Subdistrict Jebres, Surakarta. Method: This observational analytic which used cross sectional method was held in June-July 2014. The subjects were males 45 years old or older who lived at Subdistrict Jebres, Surakarta. Sixty males who were chosen by purposive random sampling method as the subjects consisted of 30 males with andropause and 30 males without andropause. Data collected through questionarie were analyzed with Chi-Square and Odds Ratio. Result: The analysis showed that 20 out of 30 males with andropause had depression. But, only 7 out of 30 males without andropause had depression. The data analysis with ? = 0.05 showed p = 0.001 (p < 0.05); Odds Ratio = 6.571. There was a significant difference of depressions occurrence between males with andropause and males without andropause at Subdistrict Jebres, Surakarta. Conclusion: There is influence of andropause on incidence of depression in males at Subdistrict Jebres, Surakarta which the number of depression prevalence is bigger at andropauses group. Keywords: Andropause, depression, males